Effects of the Central Unit Structure, Lateral Substitution and Symmetry on the Mesomorphic Behavior of Some Bent‐Core Azoester Derivatives - Catalina‐Ionica Ciobanu; Elena‐Luiza Epure; Laurentiu Soroaga; Aurel Simion; Gabriela Lisa; Irina Carlescu (ChemistryOpen, 2025)
Abstract We report here the synthesis and characterization of some new bent‐core asymmetric compounds derived from resorcinol whose thermal behavior has been analyzed by comparison with their analogs derived from 1,3‐disubstituted benzene and 2,7‐dihydroxynaphthalene containing azoester aromatic units and alkyl chain end. The asymmetric structures contain 4‐(4‐alkyloxyphenylazo)‐benzoyl and 4‐methoxy‐benzoyl or 3‐bromo‐4‐methoxy‐benzoyl as side arms. The investigations have been carried out to reach a better understanding of the structure‐properties relationship in such bent‐shaped compounds. We observed that a change in molecular structure like the nature of the central core, the symmetry of the structure or the presence of polar lateral substituent influence not only liquid crystalline properties, but also the thermal behavior. The thermogravimetric analysis showed that the bent‐core derivatives have a good thermal stability since the degradation of the compounds begins over the isotropization temperature. Theoretical calculations were performed to elucidate the behavior of the compounds. These can assist us in designing new molecules that exhibit specific mesomorphic properties.